2007
DOI: 10.1128/cvi.00046-07
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Recombinant Sao Protein Confers Protection against Streptococcus suis Infection

Abstract: Sao is a Streptococcus suis surface protein recently identified as a potential vaccine candidate. In this study, recombinant Sao in combination with Quil A provided cross-protection against S. suis serotype 2 disease in mouse and pig vaccination protocols. Subcutaneous immunization of mice elicited strong immunoglobulin G (IgG) antibody responses. All four IgG subclasses were induced, with the IgG2a titer being the highest, followed by those of IgG1, IgG2b, and IgG3. Challenge of the mice with S. suis strain 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 47 publications
3
92
2
1
Order By: Relevance
“…In contrast, IgG1 (called the "type 2 IgG subclass") elicited during interleukin-4 (IL-4)-dominant Th2 immune responses, usually has a less protective potential. Although the concept of type 1 or type 2 IgG subclasses is not well documented for pigs, recent studies have showed that porcine IgG2 had greater complement-activating capacity than IgG1 (15,16).…”
mentioning
confidence: 99%
“…In contrast, IgG1 (called the "type 2 IgG subclass") elicited during interleukin-4 (IL-4)-dominant Th2 immune responses, usually has a less protective potential. Although the concept of type 1 or type 2 IgG subclasses is not well documented for pigs, recent studies have showed that porcine IgG2 had greater complement-activating capacity than IgG1 (15,16).…”
mentioning
confidence: 99%
“…In 2007, Li et al established Sao-based ELISA for detecting titers of Sao-specific total IgG and IgG subclasses in mouse and swine sera [24] . In 2012, Hsueh et al [25] established ELISA using Sao-L and Sao-M for detecting titers of Sao-L-specific total IgG and Sao-M-specific total IgG.…”
Section: Discussionmentioning
confidence: 99%
“…The Sao protein is highly conserved among S. suis strains and Sao-specific antibodies have been shown to react with cell lysates of 28 of 33 S. suis serotypes and 25 of 26 serotype 2 isolates in immunoblots [22] . Sao protein is encoded by three allelic variants of gene of difference lengths, Sao-S (1.5 kb), Sao-M (1.7 kb) and Sao-L (2.0 kb) and Sao-M is the most common type of Sao [24] . Moreover, Sao-M in S. suis is well conserved and the protein exhibits strong immunogenicity [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations